Cultural and religious iconography projected through video mapping in urban and rural parishes of Cotopaxi (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
Iconography is important in design and digital projects, so that they allow to visualize a deeper meaning and identify elements of an artistic work and the absence of those, therefore, this research aims to analyze the iconography of video mapping of the period August 2022, so that the iconographic and iconological method of Erwin Panofsky was used, which includes a complex external and internal meaning of the modular compositions, achieving to deepen the visual aesthetic aspects, intrinsic, as well as its historical-cultural context of the urban and rural parishes of Cotopaxi, In conclusion, this case study determined that visual communication strengthens cultural knowledge by means of symbology through new technologies, which leads to determine that it is important for the new generations to know and value their roots, providing a sense of identity as belonging, which helps to understand who we are?, Where do we come from, and what is our place in the world?